An exploratory study on medications in Qatar homes - Yousif A; Kaissi RML; Wilbur K; El Hajj MS; Kheir N (Drug, Healthcare and Patient Safety, 2011)
N Kheir1, MS El Hajj1, K Wilbur1, RML Kaissi1, A Yousif21College of Pharmacy, 2College of Arts and Sciences, Qatar University, Doha, QatarBackground: Drug therapy is the most often used intervention for treatment and prevention of disease. However, if used inappropriately, drugs can cause more harm than good. Improper drug storage and disposal can have a direct impact on public safety, the environment, and the health care services. The purpose of this study was to characterize medications stored in Qatar homes and to explore their methods of storage and disposal, and to identify the public's source of information related to medicines.Methods: For the purpose of this cross-sectional exploratory study, a list of telephone numbers was generated from Qatar's telephone directory using a systematic sampling method. Individuals consenting to participate were interviewed using a multipart pretested survey instrument.Results: Data were collected from a total of 49 homes. Most respondents did not have a designated compartment or box specifically for storing medications. The majority of drugs (48%) were kept in bedrooms and a number of respondents were keeping their drugs in the fridge and in the kitchen. The most often stored classes of medicines were analgesics, antihistamines, nutritional supplements, and medications used for the respiratory system. Most respondents disposed of unwanted medicines by throwing them in the trash. In about 15% of cases, the dosage of drug taken was different from the instructions on the label. Sharing of prescription medicines was not uncommon. The majority of respondents sought information related to drugs from doctors.Conclusion: These findings raise concerns about how medications are stored and disposed of in the community. The fact that no household routinely returned unwanted medications to a pharmacy for proper disposal places the environment at risk. There is a need for more societal awareness about the safe handling and storage of drugs in the home, and about the professional role of the pharmacist.Keywords: medication, home, Qatar, storage, disposal